Characteristics of events in which police responded to overdoses: an examination of incident reports in Rhode Island - Alexandria Macmadu; Annajane Yolken; Lisa Frueh; Jai'el R. Toussaint; Roxxanne Newman; Brendan P. Jacka; Alexandra B. Collins; Brandon D. L. Marshall (BMC, 2022)
Abstract Background Narrow or non-existent Good Samaritan Law protections and harsh drug selling statutes in the USA have been shown to deter bystanders from seeking medical assistance for overdoses. Additionally, little is known about the actions that police take when responding to overdose events. The objectives of this study were to assess the prevalence and correlates of naloxone administration by police, as well as to examine overdose events where arrests were made and those in which the person who overdosed was described as combative. Methods We analyzed incident reports of police responding to an overdose between September 1, 2019, and August 31, 2020 (i.e., 6 months prior to and during the COVID-19 pandemic), from a city in Rhode Island. We examined characteristics of incidents, as well as individual characteristics of the person who overdosed. Correlates of police naloxone administration were assessed using Wilcoxon rank sum tests and Fisher's exact tests, and we examined incidents where arrests occurred and incidents in which the person who overdosed was described as combative descriptively. Results Among the 211 incidents in which police responded to an overdose during the study period, we found that police administered naloxone in approximately 10% of incidents. In most incidents, police were the last group of first responders to arrive on scene (59%), and most often, naloxone was administered by others (65%). Police were significantly more likely to administer naloxone when they were the first professionals to arrive, when naloxone had not been administered by others, and when the overdose occurred in public or in a vehicle. Arrests at overdose events were rarely reported (1%), and people who overdosed were rarely (1%) documented in incident reports as being 'combative.' Conclusions Considering these findings, ideally, all jurisdictions should have sufficient first responder staffing and resources to ensure a rapid response to overdose events, with police rarely or never dispatched to respond to overdoses. However, until this ideal can be achieved, any available responders should be dispatched concurrently, with police instructed to resume patrol once other professional responders arrive on scene; additionally, warrant searches of persons on scene should be prohibited.